O recurso extraordinário e a tutela dos direitos fundamentais - Barros, Fabrício Barbosa (2007)
This study has the purpose of demonstrating that the processual view of the Constitution provides elements for a enforced application of its dispositions, considering the existence of a urgent discipline of achievement, characterized by well defined functions: the abstract constitutionality control of the laws and the protection of fundamental rights. In order to comprehend the problem, the main aspects of the abstract constitutionality control of the laws were presented and immediatily followed by an analysis of the essential data of the fundamental rights, valuable information for the relevant role develop in strengthening the regime of democracy, demanding for its protection effective processual instruments. This examination leads to the study of the extraordinary appeal (recurso extraordinário), part of the constitutional jurisdiction model of 1988 Brazilian Constitution, but that does not have beeing associated with the fundamental rights protection. Upon these circumstances, it must be said that the omission in studies concerning the relation between the extraordinary appeal (recurso extraordinário) and the protection of fundamental rights is not in concert with the inherent nature of this processual instrument, endorsed by the Brazilian Supreme Court jurisprudential practice. Moreover, its connection to a concrete case, specially for being a diffuse constitutional jurisdiction expression, has juridical identity with the fundamental rights, in face of the limitation of the the abstract constitutionality control and the unique interpretation tools used when applying the fundamental rights.